Analysis of Bank Health During The Covid19 Pandemic in Indonesia, Using the Rgec Method - Siti Mar'atus; Agus Sukoco; Hepy Octalia Elfa Kolina (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to analyze the level of healthState-owned banks and private banks for the period 2018-2020 are viewed based on the overall RGEC (Risk profile, Good Corporate Governance (GCG), Earnings, Capital) aspects. This Type of Researchusing a qualitative approachtodataquantitative with research subjectsState-owned banks and private banks for the period 2018-2020. The data was obtained based on the document techniquementation. The data analysis technique used is the assessment of the soundness of the bankusing RGEC factors. Research resultfind that the soundness of the BankBUMN with (1) Risk Profile aspectusing the NPL ratio of